Knowledge about von Willebrand's disease among dental students - Isabella Lima Arrais Ribeiro; Adolfo Saraiva de Miranda Luna; Ana Caroline Melo de Queiroz Oliveira; Ricardo Dias de Castro (Editorial Ciencias Médicas, 2018)
Introduction: The Von Willebrand Disease is the most common bleeding disorder, and is still underdiagnosed for several reasons, including lack of knowledge about the disease. Purpose: The aim of the present study was to assess the knowledge that students attending the last year of an undergraduate dentistry programme had about dental care for patients with Von Willebrand's disease. Methods: a questionnaire containing objective questions was administered to 87 students to gather data on the following variables of interest: gender; programme term; knowledge about VWD; knowledge about the coagulation factor involved in VWD; tests to diagnose VWD; signs and symptoms of VWD; procedures required during care of VWD patients; and medications that should be avoided. The data were analysed using IBM SPSS (21.0) at a significance level of 5%. Results: 87 students responded to the questionnaire. Only 21 students (21.14%) reported having some knowledge about Von Willebrand's Disease: 49.02% correctly answered which coagulation factor is involved in Von Willebrand's Disease, and 29.4% correctly answered the question on diagnostic testing. Conclusion: Students attending the last year of an undergraduate dentistry programme have limited knowledge about Von Willebrand's Disease.